2023
DOI: 10.1093/hsw/hlad001
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Care Needs of Women with Breast Cancer: Body Image, Self-Esteem, Optimism, and Sexual Performance and Satisfaction

Abstract: As breast cancer is on the rise, it is essential to understand the consequences of the diagnosis for patients. This article investigates whether there are differences in different psychosocial variables in Spanish women with breast cancer according to the type of surgery the patients underwent and in comparison with a control group. A study was carried out in the north of Spain in which 54 women participated (27 women were the control group, and 27 women who had been diagnosed with breast cancer). The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Considering that depressive symptoms can be heterogeneous, factors of depressive symptoms may vary according to the characteristics such as sex, race, education level [ 43 , 44 ]. As breast cancer primarily affects female patients, women bear the brunt of the challenges posed by this specific cancer [ 46 , 47 ]. Moreover, the survival period for breast cancer is typically long, leading to various concerns about life [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that depressive symptoms can be heterogeneous, factors of depressive symptoms may vary according to the characteristics such as sex, race, education level [ 43 , 44 ]. As breast cancer primarily affects female patients, women bear the brunt of the challenges posed by this specific cancer [ 46 , 47 ]. Moreover, the survival period for breast cancer is typically long, leading to various concerns about life [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…43,44 As breast cancer primarily affects female patients, women bear the brunt of the challenges posed by this specific cancer. 46,47 Moreover, the survival period for breast cancer is typically long, leading to various concerns about life. 48 Particularly, young breast cancer patients face substantial challenges, particularly relating to self-image and parenting concerns.…”
Section: Discussionmentioning
confidence: 99%
“…A further longitudinal study with young breast cancer patients found that vaginal atrophy, dryness, and dyspareunia increased the risk of developing sexual dysfunction (Ganz et al, 2003). A Spanish study with breast cancer patients and a general population control group showed that the group differences in sexual satisfaction (d = 1.56; lower scores in the cancer group) were markedly higher than the differences in body image (d = 0.76) or self-esteem (d = 0.66; Montañés-Muro et al, 2023).…”
Section: Introductionmentioning
confidence: 98%
“…Optimism is a psychological construct characterized by a positive outlook and expectation for favorable outcomes. Optimism has been found to have a protective effect on mental health, including reducing the risk of depression 16 .…”
Section: Introductionmentioning
confidence: 99%